2018
DOI: 10.1111/jvh.12859
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and addressing hepatitis C reinfection in the oral direct‐acting antiviral era

Abstract: The availability of effective, simple, well-tolerated oral direct-acting antiviral (DAA) hepatitis C regimens has raised optimism for hepatitis C virus (HCV) elimination at the population level. HCV reinfection in key populations such as people who inject drugs (PWID) and HIV-infected men who have sex with men (MSM) however threatens the achievement of this goal from a patient, provider and population perspective. The goal of this review was to synthesize our current understanding of estimated rates and factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
56
2
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 42 publications
5
56
2
3
Order By: Relevance
“…Lastly, to date, this is the largest and only population-based study of HCV reinfection rates after SVR with all-oral, interferon-free therapies [11]. Using linked laboratory and administrative data has provided a strong foundation for population-level monitoring of HCV reinfection rates, which will help support the program planning required to achieve WHO HCV elimination goals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lastly, to date, this is the largest and only population-based study of HCV reinfection rates after SVR with all-oral, interferon-free therapies [11]. Using linked laboratory and administrative data has provided a strong foundation for population-level monitoring of HCV reinfection rates, which will help support the program planning required to achieve WHO HCV elimination goals.…”
Section: Discussionmentioning
confidence: 99%
“…However, as HCV infection does not result in sterilizing immunity, individuals with ongoing risk activities remain vulnerable to reinfection following cure of their initial infection [9]. Thus, reinfection after successful HCV treatment is an important public health issue and may impact efforts to control HCV transmission [10,11]. PWIDs have been shown to be adherent to DAA treatments and can be effectively cured [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, injection drug use, the predominant risk for HCV transmission, has increased in concert with the nation’s opioid epidemic . Moreover, among persons successfully treated and cured, active drug injection poses a major risk of reinfection …”
mentioning
confidence: 99%
“…(8) Moreover, among persons successfully treated and cured, active drug injection poses a major risk of reinfection. (9) Since the development of direct-acting antiviral drugs (DAAs) that offer curative treatment to persons diagnosed with HCV infection, several studies have identified important gaps in the HCV care continuum, that is, the steps along the pathway from identifying persons with active infection through to cure. National estimates suggest that in 2013, among the estimated 3.2-3.5 million persons in the United States with chronic HCV infection, roughly 50% were aware of their diagnosis, up to 38% were referred to an HCV provider, between 20% and 27% received confirmatory HCV RNA testing, 17% underwent a liver biopsy, only 7%-16% were treated, and less than 10% achieved sustained virologic response (SVR) (i.e., cure).…”
mentioning
confidence: 99%